2013
DOI: 10.1108/fs-03-2012-0011
|View full text |Cite
|
Sign up to set email alerts
|

Students' attitude towards entrepreneurship: does gender matter in the UAE?

Abstract: Purpose -The purpose of the study is to examine whether there is a difference in the entrepreneurial intentions among male and female students in UAE. The study is extremely relevant and interesting since females in the UAE have a higher success rate in education but this has not been translated into comparable increases in employment rates. Given the social, cultural, and religious fabric of the country's indigenous society and the rising number of female graduates, this anomaly in the corporate sector might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 55 publications
2
45
0
Order By: Relevance
“…The results of Majumdar and Varadarajan (2013) show that male and female students were equally strong in terms of their propensity to become future entrepreneurs. Female respondents showed higher risk-taking behaviour than males, which was contradictory to past research findings that have typically found females to be more conservative in risk-taking than males.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The results of Majumdar and Varadarajan (2013) show that male and female students were equally strong in terms of their propensity to become future entrepreneurs. Female respondents showed higher risk-taking behaviour than males, which was contradictory to past research findings that have typically found females to be more conservative in risk-taking than males.…”
Section: Introductionmentioning
confidence: 76%
“…In our opinion and according to other authors (Lituchy & Reavley, 2004;Kim & Vonorts, 2014;Caliendo et al 2014) successful business is inevitably associated with acceptance of some degree of risk. Veber et al (2005) and other authors show that the most important personality traits of the entrepreneurs seem to be honesty and creativity (Hines, 2004), conscientiousness (Zhao & Seibert, 2006), responsibility (Beugelsdijk & Noorderhaven, 2005), optimism (Frese & Gielnik, 2014) and initiative (Bruttel & Fischbacher, 2013) in addition to the aforementioned risk-taking (see also Lituchy & Reavley, 2004;Majumdar & Varadarajan, 2013;Kepler & Shane, 2007).…”
Section: Ss: Entrepreneurs Minimise Negative Influence Of Financial mentioning
confidence: 99%
“…A similar study by Ali, Topping and Tariq (2010) on Pakistani students also argues no difference in entrepreneurial intention between genders. A further study from Majumdar and Varadarajan (2013) comparing entrepreneurial intention among male and female students in the United Arab Emirates argued that both male and female students in the UAE have a higher propensity to become an entrepreneur. A study by Göksel and Aydıntan (2011) argued no difference in the influence of entrepreneurial education and gender on the intention of students to become entrepreneurs in the Turkish context.…”
Section: Previous Findings Concerning the Influence Of Entrepreneuriamentioning
confidence: 99%
“…EEP is important in producing entrepreneurs who have all the necessary knowledge and skills in conducting a business [12]. Often supported by government policy, formal EEP is sometimes made a mandatory program in higher learning institutions in countries such as Canada [13], Singapore [14], UAE [15], Turkey [16], the Netherlands [17] and Germany [18]. Even so, a contradictory view of the role of EEP was argued [18], whereby education and exposure on the actual entrepreneurship experience were seen to supersede indoctrination.…”
Section: Introductionmentioning
confidence: 99%